If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x-2)+4x=29-3(1-x)
We move all terms to the left:
-7(x-2)+4x-(29-3(1-x))=0
We add all the numbers together, and all the variables
-7(x-2)+4x-(29-3(-1x+1))=0
We add all the numbers together, and all the variables
4x-7(x-2)-(29-3(-1x+1))=0
We multiply parentheses
4x-7x-(29-3(-1x+1))+14=0
We calculate terms in parentheses: -(29-3(-1x+1)), so:We add all the numbers together, and all the variables
29-3(-1x+1)
determiningTheFunctionDomain -3(-1x+1)+29
We multiply parentheses
3x-3+29
We add all the numbers together, and all the variables
3x+26
Back to the equation:
-(3x+26)
-3x-(3x+26)+14=0
We get rid of parentheses
-3x-3x-26+14=0
We add all the numbers together, and all the variables
-6x-12=0
We move all terms containing x to the left, all other terms to the right
-6x=12
x=12/-6
x=-2
| 9x-57=3x+27 | | 1x÷5=11 | | 9x+25=8x+42 | | x+3/x-2-1x/x=17 | | ((6/7+h)-(6/7))/h=0 | | 7p+2=3(4-p) | | 5x^2-12x+39=0 | | 4x+3(-26/9)=26 | | 1-1.3x+0.4x^2=0 | | 2(x+1/2)=11 | | 5(a-7)=2(2a+1) | | 49-3w=3w+7 | | −3(2x−1)=15 | | 35x-25=15 | | 2/3-5=x+6/12 | | 3(1+6x)=5(2x-1) | | 145/5=(x+8)/5 | | 4x+1.2=4x+0.2 | | 1x+3x=5 | | 3b+(−12)=−24 | | 1/5(m+2)=3/5-m | | 1/3+x/5=16/3x^2 | | 58/x=2 | | 241=187-y | | 2x+4x=1 | | -10-(-11)=x | | 2x+4x=11x+3x=5 | | y=0.1(1.23)^8 | | 249=29-x | | 3x(x-2)=8x^2-7x | | -4.8(x-3.75)=144.4 | | x+1.62=7.57 |